Self-objectification and body dissatisfaction among the youth in Phalaborwa, Limpopo Province - Maanaso, Mokhosana Sylvester (My University, 2023)
The prevalence and co-occurrence of self-objectification and body dissatisfaction have become a noteworthy concern the world over, breaking demographic and sociocultural barriers such race, age, gender, sexuality, socio-economic background, and education level. Self-surveillance has also been shown to prevail where self objectification and body dissatisfaction are concerned. However, there is limited research that investigates the role of cultural identity in the relationship between these phenomena. This study investigated how self-objectification interrelates with self-surveillance and body dissatisfaction within a sample of 168 participants, comprising of youth aged between 14 and 24. More importantly, the study investigated the mediational role of self-surveillance and cultural identity in the relationship between self-objectification and body dissatisfaction. This cross sectional, quantitative study showed that neither self-surveillance nor cultural identity was shown to have any mediational effect on the relationship between self objectification and body dissatisfaction. Specifically, the indirect effects of SOBBSOP on Body dissatisfaction through both Self-surveillance and Cultural identity were not different to zero (CI = -.063 to .077 and -.064 to .086, respectively); and, the indirect effects of Self-objectification on Body dissatisfaction through both Self surveillance and Cultural identity were not different to zero (CI = -.040 to .072 and .077 to .066, respectively). As such, the results failed to support the predictions of the present study. It is recommended that future studies on the topic should focus on increasing sample size. Also, it is necessary to validate the scales for use in an African context, and rule out the possibility that lack of scale validation may have contributed to the outcomes.
Thesis (M. A. (Clinical Psychology)) -University of Limpopo, 2022
Keywords: Self-objection; Body dissatisfaction; Youth; Phalaborwa; Limpopo Province; Cultural policy; Socio-economic background; Manners and customs; Self-doubt